PERANCANGAN PUSAT STUDI KONSERVASI HUTAN BAKAU DI KABUPATEN CILACAP SEBAGAI FASILITAS EDUKASI DAN WISATA DENGAN PENDEKATAN REKREATIF EDUKATIF - Haqqin, Qinan Nuril (Jurnal Arsitektur ZONASI, 2021)
Indonesia has the potential for natural resources in the form of mangrove forests that grow in coastal areas. One of the areas that have the potential of natural resources is on the island of Central Java in Cilacap Regency, the area is named Segara Anakan. It's just that the more time develops the less quality due to some things that eventually lead to the problem of ecosystem degradation. To prevent further damage, and as a step to improve existing mangrove ecosystems, conservation activities are urgently needed. Conservation tries to maintain existing ecosystems for the survival of the ecosystem itself as well as the surrounding ecosystems. Conservation are very closely related to adequate facilities and infrastructure to help the activities contained in it. These facilities and infrastructures can be found in the building of the Study Conservation Center. Especially for conservation areas with mangrove ecosystem communities that can be functioned for educational activities, can also be used for recreational facilities for all society. This is also done in addition to facilitating the course of conservation activities as well as a form of introduction to new design objects that can combine educational and recreational functions to attract more attention from all circles.